Development of an Eclipse plug-in for using the LEGO Mindstorms EV3 in education - Rodriguez Perez, Simon; Fatoum, Ahmad; Abke, Jorg (IEEE Global Engineering Education Conference, 2016)
LEGO's new robot, the Mindstorms EV3, offers a range of new possibilities for education. Its most important innovation is building upon the Linux kernel for the programmable unit. LEGO has also open sourced the firmware, allowing an easy extension. Programming for a robot can give engineering students much more practical experience with technical problems and improve the learning motivation. This was the reason to include the EV3 at the university's computer science course in the studies for Mechatronics, which utilises ANSI C as the programming language. As there was - until now - no possibility to program the robot in ANSI C, an Application Programming Interface, an Eclipse plug-in and an uploader were developed. Main criteria was an easy handling of these tools. In this paper the plug-in and its integration into the computer science course is presented.